Effect of orthodontic tooth movement on salivary levels of Interleukin-1beta, Tumor Necrosis Factor-alpha, and C- reactive protein - Saadi, Noor; Ghaib, Nidhal H (Journal of Baghdad College of Dentistry, 2013)
Background: Orthodontic force is considered to stimulate cells in the periodontium to release many mediators such as cytokines which play a responsible role for periodontal and alveolar bone remodeling, bone resorption and new bone deposition. Aim of this study was carried out to estimate changes of the (interleukin-one beta, tumor necrosis factor – alpha and C-reactive protein) levels in unstimulated whole saliva during the leveling stage of orthodontic tooth movement.Materials and methods: The sample consisted of thirty adult patients (12 males and 18 females) with ages ranges (19-23) years. Each sample had Class I and Class II malocclusion dental classification and required bilateral extraction of their maxillary first premolars, underwent a session of professional oral hygiene and received oral hygiene instructions before and during the period of study, one month later fixed orthodontic appliance were placed in the upper arch by using 0.014 nickel titanium arch wire. The unstimulated whole saliva was taken from each sample immediately before placement of the appliance (baseline), and at (after1hour, after one week and after two week) following placement of the fixed orthodontic appliance. In addition the plaque index and gingival index were recorded during the interval periods of this study to assess oral cleanliness. The interleukin – one beta and tumor necrosis factor-alpha were determined by enzyme linked immunosorbent assay, while the C-reactive protein was determined by latex agglutination. Results: The results of the present study found the mean value of both salivary (interleukin-one beta and tumor necrosis factor -alpha) were highest at (after1hour) followed by at (after one week) then at (after two week) than the baseline with highly statistical significant differences (P< 0.01) among males, females and total samples, in addition there were no statistical significant differences between males and females (P>0.05). While the mean values of C-reactive protein were higher at (after 1hour) only with highly significant differences (P< 0.01) among females and total samples while only significant difference (P